Long-term natural flow regime (spells) analysis for water treatment discharges - О. Makarynskyy; D. Makarynska (Український гідрометеорологічний журнал, 2019)
Conducting mineral extraction activities usually requires obtaining a set of permits for each of the activities planned to be undertaken. This directly concerns water management and discharges associated with any mineral extraction operations. In response to the growing demand for energy resources worldwide, the industry demand for permits relating to the extraction of coal seam (and shale) gas also increased dramatically. This was in turn accompanied by the growing community concerns in regard to fracking and wastewater management practices.